2020
DOI: 10.1111/asj.13435
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan associated with whole raw soybean in diets for Murrah buffaloes on ruminal fermentation, apparent digestibility and nutrients metabolism

Abstract: This study aimed to investigate the effects of chitosan and whole raw soybean on nutrient intake, apparent digestibility, nitrogen utilization, microbial protein synthesis, blood metabolites, feeding behavior, ruminal fermentation, digesta kinetics, and reticular flow of nutrients of buffaloes. Four ruminally-cannulated Murrah buffaloes (351 ± 15 kg of initial BW) were randomly assigned according to a 4 × 4 Latin square design. Treatments were arranged as 2 × 2 factorial arrangement: the first factor was whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…Rumen pH values were not modified, maybe because of the low grain (starch) included in rations and the rumen buffering activity, and therefore, populations of fibrolytic bacteria were not affected. Hence, the apparent digestibility of NDF showed no effect, which agrees with previous experiments in buffaloes [56].…”
Section: Rumen Fermentation Parameterssupporting
confidence: 92%
“…Rumen pH values were not modified, maybe because of the low grain (starch) included in rations and the rumen buffering activity, and therefore, populations of fibrolytic bacteria were not affected. Hence, the apparent digestibility of NDF showed no effect, which agrees with previous experiments in buffaloes [56].…”
Section: Rumen Fermentation Parameterssupporting
confidence: 92%
“…There was no significant difference in the effect of chitosan supplementation on ruminal pH (Dias et al 2020); the same condition was found in this study. With an average pH value of 6.49 for all treatments, this pH is in the normal range suggested by Kong et al (2010), and the pKa of the molecules is 6.3-6.5.…”
Section: Discussionsupporting
confidence: 87%
“…After the maximum rate of degradation is reached, the size of the potentially degradable and non-degradable fractions would no longer change. The characteristics of the substrate would then be the only factor considered after that (Dias et al 2020). Higher protein content in TMR silage treated with chitosan influences higher crude protein digestibility among other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing propionate concentrations with the inclusion of CHI and CNSLt in the ruminant diet has been described by several authors (Mitsumori et al, 2014;Branco et al, 2015;Henry et al, 2015;Dias et al, 2017;Dias et al, 2020). This increase in ruminal propionate concentration is attributed to the antimicrobial characteristics of CHI and CNSLt (Henry et al, 2015;Konda et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…Chitosan is the most important derivative of chitin, the second most important natural biopolymer in the world, extracted from crustaceans, shrimps, and crabs (Pedro et al, 2020). It has been shown to have the ability to decrease methane emission by up to 42% (in vitro study; Belanche et al, 2016a;Harahap et al, 2020), increase propionate concentration (Dias et al, 2020;Dias et al, 2017), and act as a ruminal fermentation modulator (Goiri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%